Mutations in mitochondrial DNA causing tubulointerstitial kidney disease. - Thomas M Connor; Simon Hoer; Andrew Mallett; Daniel P Gale; Aurora Gomez-Duran; Viktor Posse; Robin Antrobus; Pablo Moreno; Marco Sciacovelli; Christian Frezza; Jennifer Duff; Neil S Sheerin; et al. (PLoS Genetics)
Tubulointerstitial kidney disease is an important cause of progressive renal failure whose aetiology is incompletely understood. We analysed a large pedigree with maternally inherited tubulointerstitial kidney disease and identified a homoplasmic substitution in the control region of the mitochondrial genome (m.547A>T). While mutations in mtDNA coding sequence are a well recognised cause of disease affecting multiple organs, mutations in the control region have never been shown to cause disease. Strikingly, our patients did not have classical features of mitochondrial disease. Patient fibroblasts showed reduced levels of mitochondrial tRNAPhe, tRNALeu1 and reduced mitochondrial protein translation and respiration. Mitochondrial transfer demonstrated mitochondrial transmission of the defect and in vitro assays showed reduced activity of the heavy strand promoter. We also identified further kindreds with the same phenotype carrying a homoplasmic mutation in mitochondrial tRNAPhe (m.616T>C). Thus mutations in mitochondrial DNA can cause maternally inherited renal disease, likely mediated through reduced function of mitochondrial tRNAPhe.